2018
DOI: 10.1128/iai.00186-18
|View full text |Cite
|
Sign up to set email alerts
|

Platelets Enhance Dendritic Cell Responses against Staphylococcus aureus through CD40-CD40L

Abstract: is a major human pathogen that can cause mild to severe life threatening infections in many tissues and organs. Platelets are known to participate in protection against by directly killing and enhancing the activities of neutrophils and macrophages in clearing infection. Platelets have also been shown to induce monocyte differentiation into dendritic cells and to enhance activation of dendritic cells. Therefore, in the present study, we explored the role of platelets in enhancing bone marrow derived dendritic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…Expression of CD40L on platelets has been shown to affect dendritic cells as well as B and T lymphocytes, suggesting that it provides a communicative link between innate and adaptive immunity [ 44 46 ]. For example, platelets inhibit dendritic cells differentiation in a CD40L-dependent manner and significantly suppress the proinflammatory cytokines production [ 47 ].…”
Section: Platelet Cd40l (Cd154)mentioning
confidence: 99%
“…Expression of CD40L on platelets has been shown to affect dendritic cells as well as B and T lymphocytes, suggesting that it provides a communicative link between innate and adaptive immunity [ 44 46 ]. For example, platelets inhibit dendritic cells differentiation in a CD40L-dependent manner and significantly suppress the proinflammatory cytokines production [ 47 ].…”
Section: Platelet Cd40l (Cd154)mentioning
confidence: 99%
“…In addition, IL-27 from APCs reduces the pH of phagolysosomes which boosts the ability of DCs to kill intracellular bacteria [ 32 ]. Moreover, activated platelets can stimulate DCs via CD40L production and improve their maturation, increasing cytokine secretion as well as antigen presentation in case of S. aureus infection [ 33 ].…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…For example, platelet CD40L induces production of IL-6 and IL-12 from DCs as well as increasing their expression of CD80, CD86 and ICAM-1 [ 7 ]. It has also been demonstrated that platelet-CD40L can enhance DC maturation and their ability to directly kill Staphylococcus aureus which leads to efficient adaptive immunity against the bacterium [ 111 ]. Furthermore, platelet CD40L can induce isotype switching in B-cells and augments CD8+ T-cell responses; hence, functioning as a bridge to the adaptive immune system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelets can directly interact with DC via CD62P/CD162 and this influences DC maturation and enhances their production of the Th2 helper chemokine CCL17 [ 139 , 140 ]. Alternatively, direct CD40/CD40L-dependent interactions between platelets and DC increases the latter’s ability to uptake and kill bacteria [ 111 ]. In addition, firm adhesion of platelets to DCs through MAC-1 (integrin alfaMbeta2, CD11b/CD18,) and Junctional Adhesion Molecule-C (JAM-C) leads to enhanced phagocytosis [ 141 , 142 ].…”
Section: Introductionmentioning
confidence: 99%